(untitled) (International Journal of Pharmaceutical Sciences and Drug Research, 2023)
The present study aimed to screen different extracts of Diospyros malabarica leaves for antiinflammatory and wound-healing effect in mice. Phytochemical screening of different extracts i.e. petroleum ether, chloroform, ethyl acetate, ethanol and aqueous extracts, were performed using different chemical test. All extracts were subjected to study antiinflammatory effects using xylene-induced edema and wound healing activity using an incision wound model. Antiinflammatory potential was recorded by observing the mice’s percent inhibition of edema, nitric oxide (NO) estimation, and myeloperoxidase (MPO) action. The wound healing effect was observed by measurement of tensile strength, protein level and hydroxyproline level in the wound tissues. Observation of phytochemical study was confirmed that ethanolic extract of D. malabarica leaves contains glycosides and flavonoids as major chemical constituents. Antiinflammatory effect was confirmed by significant (p<0.05) percent inhibition of ear edema, significant reduction of NO level and MPO level of mice by ethanol extract of D. malabarica leaves. Wound healing potential was observed by the significant increase in tensile strength of wound tissue after treatment with ethanolic extract. A significant (p<0.05) increase in protein and hydroxyproline level of tissue were observed after treatment with ethanolic extract of D. malabarica. In conclusion, the potent antiinflammatory and wound healing effects of ethanolic extract of D. malabarica may be observed due to the presence of glycoside and flavonoid components.